2013
DOI: 10.1002/jmv.23672
|View full text |Cite
|
Sign up to set email alerts
|

Clinico‐pathological significance of hepatitis C virus core antigen levels in chronic infection

Abstract: Hepatitis C virus core antigen (HCVcoreAg) may be measured in serum with a sensitive, recently validated assay. Beyond its value as a marker of viral infection, there are little data on its relation with clinical, histological, and virological parameters. In this study, the significance of HCVcoreAg levels was studied in a prospective cohort of 114 patients with chronic hepatitis C. HCVcoreAg was measured by a commercial chemiluminescent microparticle immunoassay. Clinical and virological data included quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
(22 reference statements)
2
10
2
1
Order By: Relevance
“…In the context of HCV/HIV coinfection, emerging data have suggested that multiple conditions, including increases in profibrogenic cytokine expression and secretion, enhancement of oxidative stress production, and increases in hepatocyte apoptosis all contribute to accelerated fibrosis [32]. In contrast to previous studies, our results did not demonstrate the correlation between HCVcAg concentration and liver inflammatory activity and liver fibrosis [33]. …”
Section: Discussioncontrasting
confidence: 56%
“…In the context of HCV/HIV coinfection, emerging data have suggested that multiple conditions, including increases in profibrogenic cytokine expression and secretion, enhancement of oxidative stress production, and increases in hepatocyte apoptosis all contribute to accelerated fibrosis [32]. In contrast to previous studies, our results did not demonstrate the correlation between HCVcAg concentration and liver inflammatory activity and liver fibrosis [33]. …”
Section: Discussioncontrasting
confidence: 56%
“…Concluded that the correlation coefficient between HCV-Ag and bDNA was 0.713 and this could be explained by that these results were based on calculations with absolute and not logarithmically transformed values. We used logarithmic transformation of HCV RNA values as wide range of the previous studies used it which is also common practice in the clinical assessment of chronic hepatitis HCV core Ag levels were correlated also with ALT levels (0.205; P < 0.04) and this in agreement with Durante-Mangoni et al [14]. who studied in a prospective cohort of 114 patients with chronic hepatitis whoever this study included genotype 1,2 and 3 only not in genotype 4 as in our study.…”
Section: Discussionsupporting
confidence: 81%
“…and Durante‐Mangoni et al. [9,13], both showed stronger correlation of genotype 2 (r = 0.77 and r = 0.65 respectively) with HCV molecular assay than genotype 1 (r = 0.72 and r = 0.53 respectively). Of note, the correlation coefficients of both genotype 1 and genotype 2 in both of these studies are considerably lower than our study, indicating there remains inconsistency amongst studies in the efficacy of HCV‐Ag immunoassays in genotyping HCV RNA positive patients.…”
Section: Discussionmentioning
confidence: 86%